2022
DOI: 10.1177/13591045211061800
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the DSM-5 Diagnostic Interview Schedule for Children, Adolescents, and Parents-5 in externalizing disorders and common comorbidities

Abstract: The Diagnostic Interview Schedule for Children Adolescents and Parents (DISCAP) is a semi-structured diagnostic interview for assessing psychiatric disorders in children and adolescents. Changes to diagnostic criteria introduced in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) required the DISCAP to be revised accordingly. The aim of this study was to evaluate the reliability and validity of the updated DISCAP-5 in clinic-referred children. The DISCAP-5 was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Even as we chose this tool, which have been extensively used, we were aware of the dialogue on the validity. On the one hand, it has been argued that tools such as the DIS, may provide statistical over- estimates because they leave out important information about clients' personal history, personality style, and other contextual variables while on the other hand there is evidence that it has good diagnostic value [ 12 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even as we chose this tool, which have been extensively used, we were aware of the dialogue on the validity. On the one hand, it has been argued that tools such as the DIS, may provide statistical over- estimates because they leave out important information about clients' personal history, personality style, and other contextual variables while on the other hand there is evidence that it has good diagnostic value [ 12 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…As with ODD, evidence continues to accrue to support the validity and utility of diagnosing CD in early childhood, and measures have been validated for CD and LPE in very early childhood. For example, the DISCAP-5 (Tissue et al, 2022) has demonstrated good concurrent and discriminant validity as well as good interrater reliability among children as young as age 2. While the concept of diagnosing a preschool child with CD with LPE might be challenging, it is important to understand that the diagnosis does not categorize the child, it categorizes a portion of the child's problematic experiences to provide for accurate conceptualization and treatment planning.…”
Section: Conduct Disordermentioning
confidence: 99%
“…When working with young children (e.g., toddler to kindergarten age), it is advisable to use interviews that are developmentally appropriate, such as the Diagnostic Interview for Children and Adolescents for Parents of Preschool and Young Children (Ezpeleta et al, 2011). The PAPA is a preschool-age version of the CAPA (noted above), and the Diagnostic Interview Schedule for Children Adolescents and Parents-5 (DISCAP-5; Tissue et al, 2022) has been validated for children as young as 2 years of age and also assesses for CD and LPE. The Diagnostic Infant and Preschool Assessment has been validated for children between 1.5 and 7 years of age in the United States (Scheeringa & Haslett, 2010), Danish (Løkkegaard et al, 2018) and Dutch (Gigengack et al, 2020) samples.…”
Section: Assessment Of Specific Dbds and Related Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The Diagnostic Interview Schedule for Children, Adolescents, and Parents, 5th Edition (DISCAP-V), 50 is a semistructured interview for assessing common childhood disorders based on the DSM-5.…”
Section: Secondary Outcome: Diagnostic Interview Schedule For Childre...mentioning
confidence: 99%